2022
DOI: 10.1038/s41467-022-34488-y
|View full text |Cite
|
Sign up to set email alerts
|

A Wolbachia factor for male killing in lepidopteran insects

Abstract: Bacterial symbionts, such as Wolbachia species, can manipulate the sexual development and reproduction of their insect hosts. For example, Wolbachia infection induces male-specific death in the Asian corn borer Ostrinia furnacalis by targeting the host factor Masculinizer (Masc), an essential protein for masculinization and dosage compensation in lepidopteran insects. Here we identify a Wolbachia protein, designated Oscar, which interacts with Masc via its ankyrin repeats. Embryonic expression of Oscar inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 39 publications
(86 reference statements)
1
43
0
Order By: Relevance
“…Other loci and mechanisms could be involved in MK, including Oscar in the expression of MK in 2 lepidopteran insects via inhibition of a protein that is essential for both masculinization and dosage compensation [ 47 ]. Our assemblies do not include any homologs of Oscar, which may not be surprising given that Oscar functions in a ZW system.…”
Section: Discussionmentioning
confidence: 99%
“…Other loci and mechanisms could be involved in MK, including Oscar in the expression of MK in 2 lepidopteran insects via inhibition of a protein that is essential for both masculinization and dosage compensation [ 47 ]. Our assemblies do not include any homologs of Oscar, which may not be surprising given that Oscar functions in a ZW system.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a novel Wolbachia protein designated Oscar was identified as a causative factor of male killing in Lepidoptera (60). The authors showed that the expression of Oscar kills males by directly targeting and degrading host Masculinizer protein required for masculinization and dosage compensation (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a novel Wolbachia protein designated Oscar was identified as a causative factor of male killing in Lepidoptera (60). The authors showed that the expression of Oscar kills males by directly targeting and degrading host Masculinizer protein required for masculinization and dosage compensation (60)(61)(62). Interestingly, Oscar contains a CifB-like domain, possibly possessing Ulp1 enzymatic activity, yet it does not seem to be essential for the male-killing function of Oscar (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pseudotakahashii system provides an opportunity to investigate the mechanism of both MK and suppression. In the current paper, the genome of the male-killer is inferred from a doubly infected individual versus one carrying the CI strain alone; the data ruled out MK mediated through one candidate gene for MK— Oscar [ 9 ]—but was consistent with another— wmk [ 10 ]. To progress this work, the genome of the MK Wolbachia strain would need to be resolved from a singly infected individual followed by functional testing of candidates through transgenic expression.…”
mentioning
confidence: 93%